Exploring the Mechanisms of Neuroinflammation: Impacts on Alzheimer’s Disease Progression and Treatment Approaches - Ali Hussein, Haider (International Journal of Psychosocial Rehabilitation, 2025)
Background: Alzheimer’s Disease (AD) is a neurodegenerative disease characterized by progressive cognitive impairment, and neuroinflammation has become a significant cause of it. Chronic activation of microglia and elevated pro-inflammatory cytokines, including Tumor Necrosis Factor-alpha (TNF-), Interleukin-1 beta (IL-1), and Interleukin-6 (IL-6), have all been linked to AD progression. In this experiment, we questioned the association between peripheral inflammatory markers and cognitive decline in AD patients. Methods: We carried out a cross-sectional study with 50 Alzheimer’s Disease patients. We collected peripheral blood for TNF-, IL-1, and IL-6. They measured brain function with the Mini-Mental State Examination (MMSE) and Alzheimer’s Disease Assessment Scale-Cognitive Subscale (ADAS-Cog). Data were then analyzed to investigate relationships between cytokine production and cognition at various stages of AD. Results: The researchers measured significantly higher TNF-, IL-1, and IL-6 in AD patients than in controls of the same age. Symptoms of AD were more severe, and cytokine levels were highest in patients with severe AD, which was strongly correlated with cognitive loss (MMSE: r = -0.68, p 0.01; ADAS-Cog: r = 0.74, p 0.01). The association of cytokine levels with disease activity shows that neuroinflammation contributes to cognitive decline in AD. Conclusion: This work also confirms that elevated peripheral cytokine levels are associated with cognitive decline in Alzheimer’s Disease (AD). These findings are evidence for the possibility that neuroinflammation is a cause of AD progression and for how neuroinflammation can be cured by targeting it. Explicit causal research at a longitudinal scale would be needed to understand why neuroinflammation is a cause of AD and why anti-inflammatory drugs slow cognitive decline.